Mechanically Induced Vasospasm‐Evaluation of Spasmolytic Efficacy of 10 Pharmaceutical Agents Using Laser Speckle Contrast Imaging. Issue 5 (1st December 2020) - Ma, Qiming; Liu, Donghong; Gong, Renyan; Chen, Shaofeng; Fang, Fang; Zhuang, Yuehong
Abstract : Background and Objectives: Vasospasm is a thorny problem often encountered in microvascular surgery that seriously threatens the survival of vascularized tissue transfers. This investigation is dedicated to establishing a model of vasospasm and to evaluating the antispasmodic efficacy of 10 pharmacologic agents. Study Design/Materials and Methods: Eighty Sprague–Dawley rats were used. After anesthesia and depilation, the femoral neurovascular bundle was exposed, and a pair of microsurgical forceps were used to trigger vasospasm of the femoral vessels by blunt dissection. Then, 10 pharmacological agents, namely, prostaglandin E1, sodium nitroprusside, magnesium sulfate, papaverine, normal saline, phentolamine, verapamil, 2% lidocaine hydrochloride, amrinone, and 12% lidocaine hydrochloride, were dripped to the femoral vessels, after which laser speckle contrast imaging was used to collect perfusion images, acquiring the perfusion and the inner caliber of the femoral vessels at multiple timepoints. Furthermore, blood perfusion and the time consumed to escape vasospasm and reach hyperperfusion in each group were calculated. The difference of spasmolytic efficacy among the agents was statistically analyzed by one‐way analysis of variance. Results: There was a significant difference in antispasmodic ability among the 10 agents ( P  < 0.001). 10% magnesium sulfate and 12% lidocaine were distinguished among the 10 agents in resolving the vasospasm. 10% magnesium sulfate demonstrated the best antispasmodic potency, which enabled the shortest time consumed for vessels to escape spasm and reach hyperperfusion. 12% lidocaine ranked second in efficacy, demonstrating a similar effect except that it could not propel the femoral vein to a state of hyperperfusion. For the remaining agents, the time consumed for the artery to escape spasm was all significantly shortened when compared with normal saline ( P  < 0.001). For the venous spasm, all agents except prostaglandin E1 could significantly shorten the time consumed for the vein to escape spasm ( P  < 0.001). Conclusions: In terms of resolving mechanically induced vasospasm, 10% magnesium sulfate is the best antispasmodic, followed by 12% lidocaine. Lasers Surg. Med. © 2020 Wiley Periodicals LLC